(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Mathematical literacy is a fundamental skill that lays the foundation for cognitive development and academic success. This article explores various mechanisms to enhance mathematical literacy in primary education. Drawing on a review of relevant literature, we discuss effective teaching methods, the role of technology, and the importance of fostering a positive attitude towards mathematics. The goal is to provide educators, policymakers, and parents with insights into practical strategies for improving mathematical literacy among primary school students. Mathematical literacy is a foundational skill that transcends the confines of the classroom, shaping cognitive abilities and problem-solving skills crucial for success in various aspects of life. In primary education, establishing a strong mathematical foundation is imperative, yet many students encounter challenges that hinder their development in this critical area. This article explores strategies and approaches aimed at improving mathematical literacy in primary education, highlighting the importance of a multifaceted and inclusive approach.